Epidemiology, use, and practice of the intraosseous route in an out-of-hospital emergency department: a retrospective cross-sectional study - Burgos-Esteban, Amaya; Quintana-Diaz, Manuel; Cordón-Hurtado, Valvanera; Giménez-Luzuriaga, Marta; Santolalla-Arnedo, Iván; de Viñaspre-Hernández, Regina Ruiz; Gea-Caballero, Vicente; Santos-Sánchez, Jose Angel; Navas-Echazarreta, Noelia; Rodríguez-Calvo, Antonio; Sánchez-Conde, Pilar; Juárez-Vela, Raúl (Frontiers in Public Health, 2024)
Introduction The Spanish Emergency Medical Services, according to the model we know today, were formed during the 80s and 90s of the 20th century. The Health Emergency Service (EMS), 061 La Rioja, began to assist the population of La Rioja in November 1999. An essential part of the mission of the SES is the provision of care and the transfer of critical patients using advanced life support unit (ALSU) techniques. In daily practice, out-of-hospital emergency services are faced with situations in which they must deal with the care of serious or critically ill patients, in which the possibility of being able to channel peripheral vascular access as part of ALSU quickly may be difficult or impossible. In these cases, cannulation of intraosseous (IO) vascular access may be the key to early and adequate care. Aim This study aimed to determine the incidence and epidemiology use of IO vascular access in SES 061 La Rioja during the year 2022. Matherial and methods We performed observational retrospective cross-sectional studies conducted in 2022. It included a population of 4.364 possible patients as a total of interventions in the community of La Rioja in that year. Results A total of 0.66% of patients showed a clinical situation that required the establishment of IO vascular access to enable out-of-hospital stabilization; this objective was achieved in 41.3%. A total of 26.1% of patients who presented with cardiorespiratory arrest (CA) were stabilized, while 100% presented with shock and severe trauma. Discussion IO vascular access provides a suitable route for out-of-hospital stabilization of critically ill patients when peripheral vascular access is difficult or impossible.